Management Approach to Manufacturing Process Technology Improvement: The Case of a Small Shipyard - Ryszard BIELSKI; Łukasz SZYSZKA; Jacek WACHOWICZ (Communications of International Proceedings, 2022)
Construction and maintenance of a fleet of ships due to climate change and consequent need for intense efforts to reduce CO2 emissions to the atmosphere became not only business, but a strategic need as well. This comes from the fact, that one of the ways of achieving this goal is the use of intermodal transport, including the use of river transport. Due to large size of vessels arise need for specific requirements in terms of measuring elements both for their construction and renovation of existing units. Based on the example of a small shipyard, this paper presents basic tools and methods of the manufacturing process which are critical for the control and quality assurance of the work performed in the shipyard. The paper proposes also their improvement by using software dedicated to measuring blocks.
Keywords: Process improvement; Small shipyard; Measurement